The Role of Reproductive Hormones in Sex Differences in Sleep Homeostasis and Arousal Response in Mice - Choi, Jinhwan; Kim, Staci J.; Fujiyama, Tomoyuki; Miyoshi, Chika; Park, Minjeong; Suzuki-Abe, Haruka; Yanagisawa, Masashi; Funato, Hiromasa (Frontiers in Neuroscience, 2021)
There are various sex differences in sleep/wake behaviors in mice. However, it is unclear whether there are sex differences in sleep homeostasis and arousal responses, and whether gonadal hormones are involved in these sex differences. Here, we examined sleep/wake behaviors under baseline condition, after sleep deprivation by gentle handling, and arousal responses to repeated cage changes in male and female C57BL/6 mice that are hormonally intact, gonadectomized, or gonadectomized with hormone-supplementation. Compared to males, females had longer wake time, shorter non-rapid eye movement sleep (NREMS) time, longer REMS episodes. After sleep deprivation, males showed an increase in NREMS delta power, NREMS time, and REMS time but females showed a smaller increase. Females and males showed similar arousal responses. Gonadectomy had only a modest effect on homeostatic sleep regulation in males but enhanced it in females. Gonadectomy weakened arousal response in males and females. With hormone replacement, baseline sleep in gonadectomized females was similar to that of intact females, and baseline sleep in gonadectomized males was close to that of intact males. Gonadal hormone supplementation restored arousal response in males but not in females. These results indicate that male and female mice differ in their baseline sleep-wake behavior, homeostatic sleep regulation, and arousal responses to external stimuli, which are differentially affected by reproductive hormones.